Biharmonic Green function of a ring domain - Vaitekhovich, Tatyana S. (MATHEMATICA SCANDINAVICA, 2010)
A biharmonic Green function of a circular ring domain R={zC: 0<r<|z|<1} is found in the form 26741 G_2(z,ζ)=|ζ-z|^2G_1(z,ζ)+h_2(z,ζ), 26741 where G_1(z,ζ) is the harmonic Green function of the ring R, and h_2(z,ζ) is a specially constructed biharmonic function.